2021
DOI: 10.30994/jqph.v5i1.265
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Counseling of Theory of Planned Behavior-Based to Increase Sufferers' Intention in Preventing Recurrent Ischemic Stroke: A Randomized Control Trial

Abstract: Introduction: Ischemic stroke has become the leading cause of premature death in the last two decades. The biggest problem in preventing recurrence ischemic stroke is the compliance of the sufferers and the obedient behavior will arise only if they are consistent and have a strong intention. This study aims to determine the effect of behavioral counseling in increasing the intention to prevent recurrent ischemic stroke by using the theory of planned behavior model approach. Methods: Randomized Control Trial wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Similar to our finding on the efficacy of the intervention in increasing “behavioral intention,” an RCT conducted in Indonesia among post-ischemic stroke patients found that TPB-based behavioral counseling was associated with a notable increase in the intention to prevent recurrent stroke at the intervention end, compared to routine care alone. [ 22 ] However, contrary to the current investigation, some studies found conflicting findings on TPB constructs. [ 21 23 40 ] In a quasi-experimental study, a 2-month stroke information campaign underpinned by TPB significantly improved the general population’s behavior of calling emergency medical services for CVA suspicion at 12 months postintervention, whereas knowledge and attitudes regarding this disease were not altered as much as expected.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Similar to our finding on the efficacy of the intervention in increasing “behavioral intention,” an RCT conducted in Indonesia among post-ischemic stroke patients found that TPB-based behavioral counseling was associated with a notable increase in the intention to prevent recurrent stroke at the intervention end, compared to routine care alone. [ 22 ] However, contrary to the current investigation, some studies found conflicting findings on TPB constructs. [ 21 23 40 ] In a quasi-experimental study, a 2-month stroke information campaign underpinned by TPB significantly improved the general population’s behavior of calling emergency medical services for CVA suspicion at 12 months postintervention, whereas knowledge and attitudes regarding this disease were not altered as much as expected.…”
Section: Discussioncontrasting
confidence: 84%
“…However, studies conducted in other countries revealed a promising capacity for TPB to be incorporated in the CVA context. [ 21 22 23 24 25 ] Hence, considering the sensitivity of education to cultural disparities, determining whether the positive outcomes of previous trials may be similar in the cultural context of Iran is of merit. Due to these reasons and considering the vital role of following healthy behaviors and self-care in rehabilitating patients who experienced CVA, this study sought to investigate the effect of a training program based on TPB regarding the self-care behavior of these patients in an Iranian context.…”
Section: Introductionmentioning
confidence: 99%
“…Alpha waves evoke relaxation, beta waves are associated with mental activity, tetha waves are associated with stressful situations and creative endeavors, while delta waves are associated with sleepiness (Tang et al, 2018). In contrast to other studies which state that to induce a sense of relaxation, counseling is needed (Adiutama, Hijriani, et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…According to a study, the formation of behavior based on belief will show lasting behavior. So, to reduce stroke-related deaths and disabilities, a better way to raise awareness among people who are at high risk is necessary (4). Efforts to prevent death or disability due to stroke, must include stroke self-awareness.…”
Section: Introductionmentioning
confidence: 99%
“…The TPB is based on a basic set of beliefs that creates an intention and causes someone to perform a specific behavior. Attitude toward behavior, subjective norms, and perceived behavior control are the primary factors in developing an individual's behavioral intention (4). A study on the TPB stated that people's views of behavioral control, attitudes toward objective and subjective norms, and intentions all have an impact on the behavior (6).…”
Section: Introductionmentioning
confidence: 99%